Innate and adaptive immunity gene expression of human keratinocytes cultured of severe burn injury - Noronha,Silvana Aparecida Alves Corrêa de (2014)
PURPOSE: Evaluate the expression profile of genes related to Innate and Adaptive Immune System (IAIS) of human Primary Epidermal keratinocytes (hPEKP) of patients with severe burns. METHODS: After obtaining viable fragments of skin with and without burning, culture hKEP was initiated by the enzymatic method using Dispase (Sigma-Aldrich). These cells were treated with Trizol(r) (Life Technologies) for extraction of total RNA. This was quantified and analyzed for purity for obtaining cDNA for the analysis of gene expression using specific IAIS PCR Arrays plates (SA Biosciences). RESULTS: After the analysis of gene expression we found that 63% of these genes were differentially expressed, of which 77% were repressed and 23% were hyper-regulated. Among these, the following genes (fold increase or decrease): IL8 (41), IL6 (32), TNF (-92), HLA-E (-86), LYS (-74), CCR6 (- 73), CD86 (-41) and HLA-A (-35). CONCLUSIONS: This study contributes to the understanding of the molecular mechanisms underlying wound infection caused by the burn. Furthermore, it may provide new strategies to restore normal expression of these genes and thereby change the healing process and improve clinical outcome.